Students’ Perceptions Of The Efficacy Of Employing The Quizizz Application In English Classroom On Synchronous Learning - Goestav Emdiansyah; Indri Astuti; Kristi Nuraini (SS&H: Studies in Social Sciences and Humanities, 2024)
Currently, developing technology encourages English teachers to be able to use several educational platforms. Quizizz is one of the educational innovations carried out to achieve learning goals. This study uses a qualitative descriptive research method. This study investigates students' perceptions of Quizizz. This study adapts and modifies the interview guide from previous research and examines two dimensions: student interest of using Quizizz and the impact of using Quizizz. Researchers conducted research at SMP Muhammadiyah Bondowoso using Quizizz as a leaning media in English lessons. Data collection was carried out utilizing questionnaire and documentation. Findings indicate positive responses regarding student interest expectations and the impact of using Quizizz expectations. However, concerns were raised regarding the limitations of question types, signal problems, and the lack of school-provided facilities